CHANGES IN THE GENERAL SECONDARY EDUCATION SYSTEM IN THE KASHKADARYA REGION IN 1924-1945. - Ne`matov Shavkatjon is the son of Boymurad (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article is devoted to the changes in the general secondary education system in the Kashkadarya region in 1924-1945 and the attitude to the education sector.